2022
DOI: 10.1108/idd-09-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the annual meetings of the association for information science and technology: analysis of two decades of published research

Abstract: Purpose The purpose of this study is to investigate the research and publication trends in the articles published in the conference proceedings of the Association for Information Science & Technology (ASIS&T) since the year 2000. Design/methodology/approach We analyzed two decades of ASIS&T proceedings to uncover bibliometric patterns. This study uses two bibliometric procedures applied to the publications in the ASIS&T conference proceedings – a bibliometrics analysis using three data source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…-unified models of information behavior (Agarwal 2022;Greifeneder & Schlebbe, 2022) -context in Information behavior (Agarwal, 2018) -analysis of JASIST proceedings (Agarwal & Islam, 2020) and ASIS&T conference proceedings (Islam & Agarwal, 2022) -theory usage in empirical research in ISIC conference papers (VanScoy et al, 2022) -metatheoretical approaches (Agarwal, 2022;Bates, 2022) -definitions for information science (panel at 2022 Information Science Summit -Agarwal, 2022b)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…-unified models of information behavior (Agarwal 2022;Greifeneder & Schlebbe, 2022) -context in Information behavior (Agarwal, 2018) -analysis of JASIST proceedings (Agarwal & Islam, 2020) and ASIS&T conference proceedings (Islam & Agarwal, 2022) -theory usage in empirical research in ISIC conference papers (VanScoy et al, 2022) -metatheoretical approaches (Agarwal, 2022;Bates, 2022) -definitions for information science (panel at 2022 Information Science Summit -Agarwal, 2022b)…”
Section: Methodsmentioning
confidence: 99%
“…and ‗scholarly communication' (50). 'Information behavior' here doesn't include the more qualified keywords like ‗information seeking behavior', 'mobile information behavior', or 'health information behavior' (Islam & Agarwal, 2022). Of the 203 empirical research papers in the 11 biennial ISIC conferences from 2000-2020, 156 used theory.…”
Section: Context In Information Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The robust nature of the bibliometric method results in studies in diverse research areas. There are a few examples as follows: innovation convergence (Cui et al, 2022), image processing (Khan et al, 2022), digital journalism research (Banshal et al, 2022), ecopreneurship (Guleria and Kaur, 2021), mucormycosis (Borgohain et al, 2022), planetary science research (Mahala and Singh, 2021), artificial intelligence (Sharma et al, 2022;Shao et al, 2022), hospitality and tourism marketing research (Liu et al, 2022), blockchain (Alam et al, 2022), gerontology research (Shen et al, 2019), maker education (Feng et al, 2022), e-government research (Ramzy and Ibrahim, 2022), gender differences (Jalal and Mukhopadhyay, 2022), data economy (Olaleye et al, 2022) and information science (Islam and Agarwal, 2022). Nove et al (2017) demonstrated that GL is extremely important across all fields.…”
Section: Bibliometricsmentioning
confidence: 99%
“…, 2019), maker education (Feng et al. , 2022), e-government research (Ramzy and Ibrahim, 2022), g ender differences (Jalal and Mukhopadhyay, 2022), data economy (Olaleye et al ., 2022) and information science (Islam and Agarwal, 2022).…”
Section: Introductionmentioning
confidence: 99%